Caracterización de la gestión administrativa y operativa del tendero de la ciudad de Tunja (2020)
The competitive world of organizations and trade in general, leads to the realization of permanent diagnostics and analysis of business and trade sectors, allowing them to implement processes and techniques to improve their productive and administrative capacity. The research aims to make a characterization of the shopkeeper in the city of Tunja, from the administrative and operational management, present in each business. The methodology is framed in the empirical‐analytical method, with a nonexperimental study there is no manipulation of variables, of quantitative type and descriptive reach, in this case, the shopkeepers of Tunja city were studied from a population of 640 storekeepers. The results show a marked empirical tendency in the administrative and operative processes, the administrators have a basic theoretical formation of the different processes that are handled in each store, this does not allow them to visualize the opportunities, neither the threats that the market offers them.